2010
DOI: 10.1111/j.1743-7563.2010.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

The use and perceived benefits resulting from the use of complementary and alternative medicine by cancer patients in Australia

Abstract: A substantial portion of Australian cancer patients use CAM. Given the limited data on efficacy and safety for most CAM, it may be reasonable to offer CAM within the hospital environment so its use can be monitored and patients can receive more evidence-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 29 publications
7
86
0
1
Order By: Relevance
“…Overall, the number of patients using CAM in this study (68%) was comparable to recent Australian studies in predominantly metropolitan cancer populations which reported CAM use in 61% and 65% of participants, respectively, 31,38 but considerably higher than that reported in a similar regional population (38%). 25 This result supports previous Australian research that CAM use is as common in rural as metropolitan areas.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, the number of patients using CAM in this study (68%) was comparable to recent Australian studies in predominantly metropolitan cancer populations which reported CAM use in 61% and 65% of participants, respectively, 31,38 but considerably higher than that reported in a similar regional population (38%). 25 This result supports previous Australian research that CAM use is as common in rural as metropolitan areas.…”
Section: Discussionsupporting
confidence: 81%
“…25,38 Prayer was used by 28% of patients, which is also comparable to recent Australian studies 25,38 ; however, a limitation of the current study is that it did not clearly distinguish between therapeutic or healing prayer and routine prayer for religious beliefs. Higher rates of acupuncture (32%) and chiropractic use (30%) were seen in the current study, 38 which may reflect regional differences in the use of these practices but may also be a result of these services being subsidized through Medicare, as well as referral to and acceptance of these services by GPs. 18 The Darling Downs region has been reported to have a high percentage of GPs who claim for acupuncture Medicare items, 40 which may also have affected this result.…”
Section: Discussionsupporting
confidence: 73%
“…A survey conducted by researchers revealed that cancer patients began using CAM alongside conventional treatment because the latter sometimes fails to cure the majority of common cancers (Scott, Kearney et al 2005). Patients also found that the CAM-based treatments are accessible, affordable and relatively safe when compared to conventional medicine (Oh, Butow et al 2010;Erku 2016) Interestingly, despite the demographic origin of the cancer patients, studies reveal that CAM users are generally well educated, with an overall higher standard of education than non-CAM users (Scott, Kearney et al 2005;Farooqui, Hassali et al 2015;Sullivan, Gilbar et al 2015). It may be that those with higher educational qualifications are more inclined to investigate the potential benefits of new or alternative therapies, especially for serious diseases such as cancer.…”
Section: Cam and Cancermentioning
confidence: 99%
“…3 In Australia, the use of CAM in cancer patients ranges from 17-65%. [4][5][6] The increasing trend in cancer patient use mirrors those of the general population and a recent study estimated 79% of cancer survivors had used at least one form of CAM in the last 12 months. 7 Additionally, 21% of non-English speaking Chinese Americans reported using CAM, particularly Chinese herbal medicine, acupuncture and Chinese massage for treating cancer related pain.…”
Section: Introductionmentioning
confidence: 99%